Low-power ternary content-addressable memory design based on a voltage self-controlled fin field-effect transistor segment. (January 2020) - Chang, Yen-Jen; Tsai, Kun-Lin; Cheng, Yu-Cheng; Lu, Meng-Rong
Abstract: Ternary content-addressable memory (TCAM) is a popular component to use for fast and parallel data searching. However, with technology downscaling, TCAM consumes huge leakage power, which affects search performance. To control TCAM's leakage power consumption, this paper proposes a multiple-segment voltage self-controlled TCAM (VoSCT) that varies the back-gate voltages of fin field-effect transistors and the supply voltages of a TCAM entry. In the VoSCT, a TCAM entry is partitioned into several segments, and each segment operates in one of the three following modes: high-speed mode, low-power mode, and ultra-low-power mode. Examples that use a real routing table are employed to verify the feasibility of the proposed VoSCT, and the experimental results indicate that 38% of leakage power and 21% of total power can be reduced with only a 9% search delay increase and 4% area overhead increase compared with the traditional TCAM design.